Inter-State Cooperation in Enforcement of International Criminal Law against Financial Crimes in the Banking Sector - Cahyad, Aep Hendar; Santoso, Edi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research investigates cooperation between countries in enforcing international criminal law against financial crimes in the banking sector. Through a qualitative approach, this research analyzes the mechanisms for identifying, implementing and evaluating cooperation between countries and the factors that influence its effectiveness. The findings highlight the important role of legal harmonization, effective communication, and increasing the capacity of law enforcement agencies in enhancing international cooperation in addressing financial crime in the banking sector. Proposed suggestions include the establishment of stronger agreements, cross-border training, and increased transparency in cooperation processes